Computed Tomography Features of Gastric Cancer Patients With DNA Mismatch Repair Deficiency - Cao, Qian; Lai, Sheng-Yuan; Xu, Nan; Lu, Yang; Chen, Shuai; Zhang, Xin-Sheng; Li, Xiang (Frontiers in Oncology, 2021)
Objective: To explore the computed tomography (CT) features of gastric cancer (GC) patients with DNA mismatch repair deficiency (dMMR). Materials and Methods: This study reviewed the clinical and CT features of GC patients with dMMR, confirmed by the postoperative results, between September 2017 and December 2019. The expression pattern of MMR major proteins (MLH1, MSH2, MSH6 and PMS2) in immunohistochemistry was used to confirm the MMR status in GC tissues. The correlation between pre-treatment CT features and MMR status was statistically analyzed. Results: A total of 28 patients with GC were diagnosed as dMMR in our study, and 49 patients were MMR-proficient (pMMR). The tumor locations were significantly different between the dMMR and pMMR groups (p=0.006). The CT tumor thickness, CT long and short diameters of the largest lymph node, and number of lymph nodes on CT of the dMMR group were significantly different from the pMMR group. Conclusion: The dMMR GC exhibited a lower stomach location, smaller tumor thickness and lymph node diameter, and fewer lymph nodes on CT imaging.